Respons ASEAN Terhadap Peredaran Narkoba Lintas Negara di Kawasan Golden Triangle - Naila Essenza Quraniq; Talitha Sani Azmi (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2025)
The transnational drug trade in the Golden Triangle region is a form of transnational crime that has envolved into a non-tradisional security threat in Southeast Asia. This phenomenon is characterized by the cross-border mobility of actors and coomplex trafficking routes, as well as the limited capacitu of states to adress it unilaterally. This condition has necesstated regional cooperation under the ASEAN framework. The research methodology employed emphasizes a qualitative approach utilizing secondary data such as literature, official websites, and reports. The analysis was conducted using international regime theory by tracing the regime formation process through three stages: agenda-setting, institutional selection, and operationalization. The analysis reveals that the dug issue has been framed as a non-traditional security threat and incorporated into ASEAN’s regional security agenda, prompting the development of the Border Cooperation Management framework as a basis for transnational crime coordination. This framework is then operationalized sectorally through the ASEAN Senior Officials on Drug Matters (ASOD).